Lenin's Jewish question - Petrovskiĭ-Shtern, Ĭokhanan (Yale University Press, 2010)
The grandson of a Jew, whose Jewish relatives converted to Christianity, whose allies played down his Jewish origins just as fervently as his enemies played them up, V.I. Lenin makes for a fascinating case study of the many complexities associated with 'Jewish question' in Russia.